‘“If I Should Fall From Grace…”: Stories of Change and Organizational Ethics - Carl Rhodes (Journal of Business Ethics, 2009)
Although studies in organizational storytelling have dealt extensively with the relationship between narrative, power and organizational change, little attention has been paid to the implications of this for ethics within organizations. This article addresses this by presenting an analysis of narrative and ethics as it relates to the practice of organizational downsizing. Drawing on Paul Ricoeur’s theories of narrative and ethics, we analyze stories of organizational change reported by employees and managers in an organization that had undergone persistent downsizing. Our analysis maintains that the presence of a dominant story that seeks to legitimate organizational change also serves to normalize it, and that this, in turn, diminishes the capacity for organizations to scrutinize the ethics of their actions. We argue that when organizational change narratives become singularized through dominant forms of emplotment, ethical deliberation and responsibility in organizations are diminished. More generally, we contend that the narrative closure achieved by the presence of a dominant narrative amongst employees undergoing organizational change is antithetical to the openness required for ethical questioning.